Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan (Studi Pada PT Telkom Indonesia Tbk) - Shita Tiara; Putri Angeline Azzuna; Adzra Dinda Dinanty; Muhammad Arif (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2026)
This study aims to analyze the financial performance of PT Telkom Indonesia (Persero) Tbk for the period 2022–2024 using financial ratio analysis. The method used is a descriptive quantitative approach with documentation techniques to collect annual financial report data. Financial ratios analyzed include the Liquidity Ratio (Current Ratio), Solvency Ratio (Debt to Asset Ratio and Debt to Equity Ratio), and Profitability Ratio (Gross Profit Margin, Return on Assets, and Return on Equity). The results show that the liquidity ratio (Current Ratio) remained below 1 throughout 2022–2023, improving to 0.82 in 2024, reflecting limited but improving short-term debt coverage. The solvency ratio remained stable, with DAR around 45–46% and DER around 83–84%, indicating controlled debt management. The profitability ratio showed a fluctuating trend, with the best performance recorded in 2023 across all indicators. Overall, PT Telkom Indonesia (Persero) Tbk's financial condition is considered stable, with adequate capacity to sustain its operational activities.